The Non-Native Students’ Motivation in Learning English at STIE Perbanas Surabaya (Language Circle: Journal of Language and Literature, 2018)
ow competence in English for the students of Non English native speakers has been crucial so far for the teachers in language teaching in Indonesia. This study attempts to explore students ‗motivation in learning English at STIE Perbanas Surabaya. This is a qualitative research and a case study. This study analyzed the data by means of a descriptive analysis. This method was chosen to describe the qualitative data taken from the students at STIE Perbanas Surabaya who were taking English subject. The data were collected using questionnaire. Some of the students were also interviewed in depth to triangualize the data related to their motivation in learning English. It was found that there are two types of motivation by the students of STIE Perbanas in learning English: intrinsic and extrinsic. They agreed (78%) that they are studying English because it is a compulsory subject in this college. Besides that, they have several factors of motivation affecting the students‘ learning English as foreign language such as local education system, attitudes to the target language, and teacher factor.